1987
DOI: 10.1007/bf00583788
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training induces transitions of myosin isoform subunits within histochemically typed human muscle fibres

Abstract: Fibre type composition based on histochemical myosin ATPase reaction was studied in cross sections of biopsies from the vastus lateralis muscle of men. In addition, protein composition as well as peptide patterns of isolated myosin heavy chains were examined in batches of individually classified fibres from the same biopsies. High intensity endurance training during 8 weeks induces significant decreases by 31-70% of the type IIB fibre population in 3 of 4 subjects (in one case no change was observed). These de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 82 publications
4
61
0
5
Order By: Relevance
“…Numerous studies of the human (2,3,4,12,13,17,20,24) have shown that skeletal muscle fiber characteristics change depending on the mode of exercise. Anaerobic exercise facilitates increases in fast-twitch muscle, while aerobic exercise facilitates increases in slow-twitch muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of the human (2,3,4,12,13,17,20,24) have shown that skeletal muscle fiber characteristics change depending on the mode of exercise. Anaerobic exercise facilitates increases in fast-twitch muscle, while aerobic exercise facilitates increases in slow-twitch muscle.…”
Section: Introductionmentioning
confidence: 99%
“…5 Endurance training between 2 and 8 weeks has been observed to reduce the size of the SC, 6,7 however it is unlikely that changes in muscle fibre distribution would have occurred during this period. 8,9 It is likely that factors either in addition to or other than muscle fibre type are contributing to the magnitude of the SC. One of these factors may include muscle oxidative capacity since the time required to decrease the magnitude of the SC is similar to the time required to increase mitochondrial enzyme activity 10,11 following endurance training.…”
Section: Introductionmentioning
confidence: 99%
“…The lung function variables, however, showed extremely significant differences, the FVC in rowers was 2.26 ± 0.28 l, and in runners, it was 3.36 ± 0.402 l, the FEV 1 in rowers was 2.005 ± 0.28 l and runners 3.18 ± 0.29 l, the MVV in rowers was 119.81 ± 22.93 l/ min, whereas in runners, it was 151.58 ± 21.24 l/min and the PEFR also shows there is a significant difference where rowers were recording 5.69 ± 1.65 l/s and runners 9.67 ±2.71 l/s. Studies of lung function in rowers are uncommon, but one study done in rowers of Kerala showed equivalent FVC as rowers in Manipur although a little lower values for FEV 1 and MVV. [3] A study on competitive runners conducted in Karnataka [4] showed a little lower lung function values than runners of this study but higher than the rowers who participated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of mass, metabolic power, [1] and strength of body muscles as a result of prolonged and especially the respiratory muscles ensure the adequate supply of oxygen as well as the adequate removal of carbon dioxide. The performance level of the sportspersons depends a great deal on the efficiency of the respiratory system and the strength of all respiratory muscles.…”
Section: Introductionmentioning
confidence: 99%